Brazilian individuals with impaired glucose tolerance are characterized by impaired insulin secretion - Pimenta, W. P.; Santos, M. L.; Cruz, N. S.; Aragon, F. F.; Padovani, C. R.; Gerich, J. E. (Masson Editeur, 2002)
Background: To better understand the pathogenesis of type 2 diabetes mellitus, insulin secretion and insulin sensitivity (IS) were evaluated in white Brazilians with impaired glucose tolerance (IGT), using the oral glucose tolerance test (OGTT) and the hyperglycemic clamp technique.Methods: Twenty-five IGT subjects were individually matched with normal glucose-tolerant (NGT) subjects for demographic characteristics, At first, they were submitted to the OGTT and plasma glucose and insulin were measured. of the 25 pairs, 20 could participate in the hyperglycemic clamp procedures, at a second visit. All participants had their plasma glucose levels equally increased to 180 mg/dl; this was maintained for three hours by variable glucose infusion. During the procedure, plasma glucose and insulin were measured at established intervals.Results: In the postabsorptive state, the IGT subjects presented higher levels of plasma glucose, blood HbA(1) and serum triglycerides, but similar plasma insulin levels. After the oral glucose load, early and total insulin release, in relation to glucose levels, were respectively, 43 and 67% lower in the IGT individuals, the index of whole-body IS was increased in the IGT individuals (4.36 +/- 1.71 vs 3.61 +/- 1.28 mg(-1).muU(-1) 100.ml(2); p < 0.05). By the hyperglycemic clamp technique first- (82 &PLUSMN; 26 vs 215 &PLUSMN; 88 μU/ml; p < 0.001) and second- (36 +/- 19 vs 73 +/- 44 muU/ml; p < 0.05) phases of insulin secretion was decreased in the IGT individuals, especially the first one. However, the groups did not differ in relation to the IS: IGT = 13.52 &PLUSMN; 7.27 and NGT = 9.96 &PLUSMN; 6.70 mg.ml/kg.μU.min(-1); p > 0.05. Functional relationship of IS (y) on first-phase insulin release (x) showed a smaller (p < 0,05) regression coefficient for the IGT group.Conclusion: Brazilians with IGT well-matched with NGT ones were characterized by impaired first- and second-phase insulin secretion (mainly the former), while defects in IS were not evident.
Keywords: impaired glucose tolerance; insulin secretion; insulin sensitivity; oral glucose stimulus; hyperglycemic clamp